Field and Numerical Investigation on the Coal Pillar Instability of Gob-Side Entry in Gently Inclined Coal Seam - Xupeng Ta; Zhijun Wan; Yuan Zhang; Peng Shi; Zejie Wei; Xin Sun; Liangliang Jia (Advances in Civil Engineering)
In order to study the coal pillar stability of gob-side entry in gently inclined coal seam, a comprehensive method including theoretical analysis, numerical modeling, and field monitoring was applied to study its fracturing and instability mechanism. The results show that the uneven horizontal stress was the internal cause of entry asymmetric deformation and failure in inclined coal seam. In gently inclined coal seam, the rotation movement of the main roof and stress distribution were closely related to inclination of the coal seam. Based on the asymmetric deformation characteristics and mechanisms of entry, a collaborative control technology of roof cutting for pressure relief and support strengthening has been put forward. The research results have practical signiﬁcance for revealing the mechanism of entry damage in gently inclined coal seam mining and proposing engineering measures to prevent coal pillar damage and disaster occurrence.